Cyberbullying Prevention Measures Through Social Media - Setyaningsih, Setyaningsih; Hidayatullah , M. Furqon; Asrowi, Asrowi; Rahman, Abdul (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Technological advances have made non-face-to-face interaction easier, but the use of gadgets and social media by teenagers often leads to negative things, for example cyberbullying, which is an increasingly serious problem. This research aims to identify cyberbullying behavior among students at SMP Negeri 3 Surakarta and efforts to prevent it. This research shows that monitoring social media, raising awareness, gathering user resources, and understanding digital platforms are effective prevention efforts. The majority of cyberbullying perpetrators are women and WhatsApp is the most frequently used social network. The forms of cyberbullying that are most often used are teasing and insults, and the most common reasons are just being fun or just following friends. The majority of respondents were victims of cyberbullying, and the perpetrator's psychological condition after experiencing cyberbullying varied from normal to regretful or even satisfied and happy. This research provides insight into the problem of cyberbullying among students at SMP Negeri 3 Surakarta and highlights the importance of prevention and education regarding its impacts.